How does for-profit college attendance affect student loans, defaults, and earnings? - Luis Armona; Rajashri Chakrabarti; Michael F. Lovenheim (Federal Reserve Bank of New York, 2017)
For-profit providers are becoming an increasingly important fixture of U.S. higher education markets. Students who attend for-profit institutions take on more educational debt, have worse labor market outcomes, and are more likely to default than students attending similarly selective public schools. Because for-profit schools tend to serve students from more disadvantaged backgrounds, it is important to isolate the causal effect of for-profit enrollment on educational and labor market outcomes. We approach this problem using a novel instrument combined with more comprehensive data on student outcomes than have been employed in prior research. Our instrument leverages the interaction between increases in the demand for college when labor demand declines and the local supply of for-profit schools. We compare enrollment and postsecondary outcome changes across areas that experience similar labor demand shocks but that have different latent supply of for-profit institutions. The first-stage estimates show that students are much more likely to enroll in a for-profit institution for a given labor demand change when there is a higher supply of such schools in the base period. Second-stage estimates vary somewhat across two-year and four-year schools. Among four-year students, for-profit enrollment leads to more loans, higher loan amounts, an increased likelihood of borrowing, an increased risk of default, and worse labor market outcomes. Two-year for-profit students also take out more loans and have higher default rates and lower earnings. But they are more likely to graduate and to earn over 25,000 per year (the median earnings of high school graduates). Finally, we show that negative local labor demand shocks induce for-profit entry and that this effect is larger in areas that have a higher latent supply of for-profit institutions. Our results point to low returns to forprofit enrollment - a finding that has important implications for public investments in higher education as well as how students make postsecondary education choices.
Keywords: H4; I2; J1; 330; postsecondary education; for-profit schools; student loans; default; returns to education